The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mop.30275
|View full text |Cite
|
Sign up to set email alerts
|

An X band patch antenna integrated with commercial triple‐junction space solar cells

Abstract: An X band patch antenna was integrated on top of the cover glass of commercial space-certified solar cell and was studied for understanding the interaction between the solar cell and the antenna. It was found that the solar cell acts as a lossy substrate for the antenna and reduces the gain of the antenna by about 2 dB, and such a reduction remains consistent for different working states of the solar cell. The patch antenna reduces the efficiency of the solar cells because it blocks light, however, at 10 GHz, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that the solar cells affect the antenna's performance as a lossy added substrate and reduce the antenna's gain by about 2 dB [19,20]. But such a gain reduction is still acceptable when considering overall satellite payload and link budget, and it can be improved by using thicker cover glass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the solar cells affect the antenna's performance as a lossy added substrate and reduce the antenna's gain by about 2 dB [19,20]. But such a gain reduction is still acceptable when considering overall satellite payload and link budget, and it can be improved by using thicker cover glass.…”
Section: Discussionmentioning
confidence: 99%
“…Although meshed patch antennas find applications in many areas [2,11], the main interest of this study is to provide a transparent antenna design to be integrated with the solar panels of Cube Satellites (CubeSats) in order to save very limited surface real estate [12,13]. Typically, the solar panel of a CubeSat has a solid metal backing (i.e., metallic shielding of the satellite), as illustrated in Fig.…”
Section: Meshed Patch Antenna Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be also applied to a patch antenna operating at any frequency band. The designed compact antenna configuration can be used in portable communication devices for X-band wireless sensor applications like different security systems, automatic door openers, automatic sensor lights, automated monitoring systems and also in solar panels [19], etc. The modifications made in the ground plane also generates an additional degree of antenna miniaturisation without affecting the phase tuning mechanism of the fixed size patch in a unit-cell configuration of the reflectarray antenna.…”
Section: Antenna Performance Comparisonsmentioning
confidence: 99%
“…The ground plane of the antenna was also made by wires in [20] (to ensure reduced shadowing), but introduced some undesired back radiation. A CP antenna made by a nearly square meshed patch fed with a coplanar Y-shaped feed, but not integrated on a solar panel, has been proposed in [21]; whereas a uniform patch antenna integrated on a cubesat has been described in [22].…”
Section: Introductionmentioning
confidence: 99%